Verifying the X for design framework capabilities in improving user experience evaluation activities - Stefano Filippi (Taylor & Francis Group, 2019)
The literature offers methods and tools for user experience (UX) evaluation. Among them, the irMMs-based method exploits mental models related to specific situations of interaction. The literature also proposes frameworks and models to describe product development activities. One of these, the X for Design framework (XfD), allows modeling different activities and suggests modifications in order to improve them. This research aims at verifying the capabilities of the XfD in improving the irMMs-based method. Once improved thanks to the XfD, the irMMs-based method is adopted together with the original release of it and with the well-known Think Aloud usability evaluation method in evaluating the UX of a CAD software package. The comparison of the results starts demonstrating the capabilities of the XfD in improving UX evaluation activities. The research outcomes can be of interest for researchers who can exploit the XfD suggestions to deepen their knowledge about human cognitive processes and for industrial practitioners who can apply the suggestions proposed by the XfD to their own evaluation activities to make them more effective.